#WeAreNotWaiting DIY artificial pancreas systems and challenges for the law. Issue 5 (21st October 2021) - Dickson, Rachael; Bell, Jessica; Dar, Amber; Downey, Laura; Moore, Victoria; Quigley, Muireann
Abstract: Commercial hybrid closed‐loop systems are becoming more readily available, yet the number of DIY artificial pancreas system (DIY APS) users continues to rise. These DIY systems have not gone through the usual regulatory approvals processes, and, thus, present a number of legal difficulties for a number of actors, including clinicians, parents who build DIY APS for their children, and users themselves. These issues have so far received insufficient attention. Due to the complex constellation of actors involved in both development of DIY APSs and in its deployment, it is not currently clear who, and to what extent, different parties might (successfully) be held liable if something goes wrong. Despite this uncertainty, unless and until clearer guidance is issued by relevant bodies, or a case appears before the courts which clarifies the situation, existing legal principles apply. In this article, we examine some of these to shed light on how the law would likely be applied if harm were to result from the use of a DIY APS.